ANALYZING THE DRUG FORMULARY USED AT THANH HOA LUNG HOSPITAL IN 2022 - Doan Lan Anh; Ha Minh Duc; Ha Thi Ngoc; Nguyen Xuan Trung; Nguyen Tuan Quang; Vu Van Dai (Tạp chí Y học Quân sự, 2026)
Objectives: To analyze the structure and ABC/VEN classification of the drug formulary used at Thanh Hoa Lung Hospital in 2022, thereby evaluating the rationality of drug use and providing a scientific basis for developing the hospital’s formulary in subsequent years. Subjects and methods: A retrospective, cross-sectional descriptive study was conducted on all drug items used at Thanh Hoa Lung Hospital from January 1 to December 31, 2022. Results: The 2022 formulary included 605 drug items with a total value of 23.16 billion VND. Pharmaceutical (chemical) drugs accounted for 96.52% in quantity and 95.50% in value; domestically produced drugs for 63.95% of value; and generic drugs for 90.09% of value. Single-component drugs accounted for 84.46% in quantity and 72.30% in value, while injectable and infusion drugs represented 60.38% of total value. According to the ABC classification, class A drugs accounted for 14.38% of items but 75.06% of value. In the VEN classification, V and E groups accounted for 87.27% of items and 93.08% of value. In the ABC/VEN matrix, group I represented 49.92% of items and 88.97% of value. Conclusions: The hospital’s 2022 formulary was generally appropriate to its disease pattern, emphasizing domestic and generic drugs. Continuous monitoring of high-cost, non-essential (AN) and injectable drugs is recommended to ensure rational, safe, and cost-effective drug use.